TANTANGAN HUKUM ADAT DALAM ERA GLOBALISASI SEBAGAI LIVING LAW DALAM SISTEM HUKUM NASIONAL - Mayasari, Riezka Eka (JOURNAL EQUITABLE, 2017)
The existence of customary law in living values in the community despite of not written so that even customary law is not defined by the State (positive) but apply in the midst of society. Customary law as an applicable law  is  not  necessarily  to  be  seen  from  the  sanctions  application,  but customary law is sufficiently declared applicable when there are statements expressed as a revelation of a sense of justice that is declared as norm, so customary law further ensures a sense of justice that it takes the community as living law in positive law in Indonesia.